Introns as Gene Regulators: A Brick on the Accelerator - Rose, Alan B. (Frontiers in Genetics, 2019)
A picture is beginning to emerge from a variety of organisms that for a subset of genes, the most important sequences that regulate expression are situated not in the promoter but rather are located within introns in the first kilobase of transcribed sequences. The actual sequences involved are difficult to identify either by sequence comparisons or by deletion analysis because they are dispersed, additive, and poorly conserved. However, expression-controlling introns can be identified computationally in species with relatively small introns, based on genome-wide differences in oligomer composition between promoter-proximal and distal introns. The genes regulated by introns are often expressed in most tissues and are among the most highly expressed in the genome. The ability of some introns to strongly stimulate mRNA accumulation from several hundred nucleotides downstream of the transcription start site, even when the promoter has been deleted, reveals that our understanding of gene expression remains incomplete. It is unlikely that any diseases are caused by point mutations or small deletions that reduce the expression of an intron-regulated gene unless splicing is also affected. However, introns may be particularly useful in practical applications such as gene therapy because they strongly activate expression but only affect the transcription unit in which they are located.